2017
DOI: 10.1515/afe-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Chromite-Based Moulding Sands Bonded with Sodium Silicate

Abstract: In the paper, a research on effects of baking temperature on chromite sand base of moulding sands bonded with sodium silicate is presented. Pure chromite sand and its chromite-based moulding sand prepared with use of sodium silicate were subjected to heating within 100 to 1200 °C. After cooling-down, changes of base grains under thermal action were determined. Chromite moulding sand was prepared with use of 0.5 wt% of domestic made, unmodified sodium silicate (water-glass) grade 145. After baking at elevated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…An alternative solution for the physical hardening of hydrated sodium silicate is the use of microwaves. Own research [13] and literature data [17,18] have shown that, at a lower content of binder, this technology enables obtaining moulding sands with a strength higher than the strength of the sands hardened with an ester hardener (Fig. 3).…”
Section: Selection Of Moulding Sands For Disposable Moulds Used In Ab...mentioning
confidence: 99%
“…An alternative solution for the physical hardening of hydrated sodium silicate is the use of microwaves. Own research [13] and literature data [17,18] have shown that, at a lower content of binder, this technology enables obtaining moulding sands with a strength higher than the strength of the sands hardened with an ester hardener (Fig. 3).…”
Section: Selection Of Moulding Sands For Disposable Moulds Used In Ab...mentioning
confidence: 99%
“…The changes that occur on the grain surface of the chromite matrix are presented in [ 18 ]. The authors found that, as the temperature increases, the grain matrix-formed layer of iron oxides becomes less and less bonded to the grain, resulting in easier chipping of these areas during the processing of moulding sands.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave hardening with fast and uniform features is used to improve the efficiency of the sodium silicate sands [1]. The strength of moulding sands is enhanced on the premise of a significant decrease in the amount of sodium silicate.…”
Section: Introductionmentioning
confidence: 99%